Basic characteristics of a multilayer thin electrostatic actuator supported by lubricating oil for a fine-motion stage - Md Ghazaly, Mariam (Elsevier, 2012)
The present paper describes the basic characteristics of a multilayer thin electrostatic actuator supported by lubricating oil rather than precise ball bearings for a ﬁne-motion stage. The purpose of the present research is to realize an easy-to-maintain multilayer thin electrostatic actuator having a simple structure for high-precision motion. Lubricating oil is used to support the mover, which is constructed of thin electrodes, andto reduce the frictionbetweenthemover andstator layerswithouttheneedforprecise ball bearings. Eachlayer ofthe actuatorhas only one simple electrode that comprises several beams.Inorder to examine the characteristics ofthemultilayer thin electrostatic actuator, a two-layer electrostatic actuator was designed and constructed. First, the effect of the viscosity of the lubricating oil on the displacement and force characteristics were examined in order to clarify the suitable lubricating oil characteristics. In the experiments, low-viscosity oil provided a faster response and a larger thrust force. Next, a suitable driving signal for the electrostatic actuator supported by lubricating oil was investigated experimentally. Based on the results, control systems for the electrostatic actuator using suitable driving signals were designed in order to examine the effectiveness of the actuator. The positioning results indicate that the positioning accuracy is better than 15 nm.